Developing Community Culture-Based Storybooks Integrating QR Codes for Children’s Writing Narrative Skills and Digital Well-Being - Jendriadi Jendriadi; Linda Eka Pradita; Musria Ekawati; Farikah Farikah; Asmendri Asmendri (Ta'dib, 2026)
Children are one of the market segments that use gadgets for. They choose the gadgets caused of their attractive features and various conveniences they provide. Parents' current concerns are because gadgets have many effects. starting from decreased social interaction and emotional instability in children. Actually, gadgets have a positive side as long as they are used for positive matters. This study focuses on designing learning media in the form of story books with barcodes by linking local traditions of the Magelang community to reduce the negative impact of these gadgets. In addition, it is hoped that children have good narrative writing skills by connecting local Magelang wisdom. Local culture will find a place in the hearts of children through storytelling activities. In addition, they are also able to retell what is in their minds through writing. This research is a Research and Development (R&D) by Thiagarajan, through four stages including: Defining, Designing, Developing, and Disseminating. Results show that the QR code-based storybook successfully captured children’s interest, encouraged more meaningful use of gadgets in learning, and improved participation in narrative writing. Moreover, the integration of cultural elements with interactive features helped guide children toward balanced digital experiences that support both literacy development and digital well-being.